EFEKTIFITAS PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT FACILITATOR AND EXPLAINING (SFAE) UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR SISWA KELAS V SD NO.8 BUNGKULAN - Komang Suryani (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
This study aims to increase the activity and learning achievement of students with theapplication of the Cooperative Learning Model Student Facilitator and Explaining Type (SFAE)can improve Class V Student Achievement in Semester II PKN Subjects at Elementary SchoolNo.8 Bungkulan 2017/2018 Academic Year. Cooperative learning model type Student Facilitatorand Explaining is a learning model that places students to present ideas or opinions to otherstudents so that students will be trained to have speaking skills and provide new ideas individuallythat can improve student learning achievement. The implementation of the Cooperative learningmodel of Student Facilitator and Explaining Type (SFAE) can improve student learning activitiesin the fifth grade elementary school students. 8 May 2017/2018 school year. The average learningactivity of students increased from 56.4 in the sufficient category in the first cycle to 75.0 in theActive category in the second cycle. The application of cooperative learning model type studentfacilitator and explaining (SFAE) can improve student learning achievement in class V SD No. 8May 2017/2018 school year. The average student achievement increases from 68.8 in cycle I to80.6 in cycle II.Keywords: Learning Model, Student Facilitator and Explaining (SFAE)